Voluntary agreements as a substitute for regulations and economic instruments: Lessons from the German voluntary agreements on CO 2-reduction - Eberhard Jochem; Wolfgang Eichhammer (Fondazione Eni Enrico Mattei (FEEM), 1997)
Voluntary agreements in various forms are being increasingly regarded as an instrument to substitute or complement regulating and pricing instruments. As, from a theoretical point of view, this instrument has strong proponents and opponents, it is important to make a careful analysis of the achievements of current voluntary agreements and their specific advantages or drawbacks in their specific objective and social context. The following paper analyses the voluntary agreements of the German economy with respect to CO2 emission targets, achievements up to 1995, the monitoring process implemented, as well as the foreseeable progress up to 2005. The analysis distinguishes among the industrial branches (where trade associations signed the declaration for their member companies), the electricity supply sector and the remaining energy sector (gas and water supply, municipal supply companies, mineral oil trade), which, for the first time, has declared reduction targets for their clients. For voluntary agreements to become as successful as regulating and economic instruments, it is important for all the parties involved to see the declarations as a process which transforms the quantitative goals into moving targets.
Keywords: 330; Treibhausgas-Emissionen; Luftverschmutzung; Unternehmenskooperation; Selbstverpflichtung; Deutschland